2017
DOI: 10.1021/acs.jpca.7b10784
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the CH Stretch/Torsion/Rotation Couplings in Methyl Peroxy (CH3OO)

Abstract: The manifestations of CH stretch/torsion/rotation coupling in the region of the CH stretch fundamentals are explored in the CHOO radical. Following our earlier study of the fundamental in the totally symmetric CH stretch (the ν fundamental), this work focuses on the other two CH stretch fundamentals, ν and ν, which would be degenerate in the absence of a barrier in the potential along the methyl torsion coordinate. The simplest model, which assumes a decoupling of the CH stretch vibrations from the torsion, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A variety of theoretical methods have been advanced for characterizing rovibrational anharmonicity, including diffusion Monte Carlo, , variational approaches, path integrals, direct product diagonalization, empirical methods, , perturbation theories, specialized methods for torsions, and other separable approaches. Many of these methods are designed for spectroscopic applications and are most reliably applied to predict high-accuracy zero point energies and fundamental transition energies. There has been relatively less work done to characterize anharmonicity at high temperatures and energies.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of theoretical methods have been advanced for characterizing rovibrational anharmonicity, including diffusion Monte Carlo, , variational approaches, path integrals, direct product diagonalization, empirical methods, , perturbation theories, specialized methods for torsions, and other separable approaches. Many of these methods are designed for spectroscopic applications and are most reliably applied to predict high-accuracy zero point energies and fundamental transition energies. There has been relatively less work done to characterize anharmonicity at high temperatures and energies.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Step-scan Fourier transform spectroscopy has been used to obtain temporally resolved IR spectra for CH 3 OO, identifying major absorption bands and characterizing the torsional splitting of the ν 1 , ν 2, and ν 9 modes. [12][13][14] Blanksby et al 15 have reported the photoelectron (PE) spectra of the CH 3 OO and C 2 H 5 OO anions, finding the electron affinities of the corresponding radicals to be 1.161 ± 0.005 eV and 1.186 ± 0.004 eV, respectively. Theà ←X electronic transitions of CH 3 OO and C 2 H 5 OO in the near-IR absorption region have been characterized by Miller and co-workers [16][17][18] using cavity ringdown spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the proposed method is promising for in situ time-resolved measurements and remote sensing to explore the issues in atmospheric chemistry and other applied sciences. Future studies can perform quantitative spectral analysis with rotationally resolved spectra of key radicals, such as organic peroxy radicals (RO 2 ) with torsion-CH stretch coupled infrared spectral features 42 . Unstable molecules, such as the simplest Criegee intermediate 2 , which has relatively weak C-H vibrational bands, can also be observed with our time-resolved dual-comb spectrometer coupled with a cavity-enhanced cell.…”
Section: Discussionmentioning
confidence: 99%